Peer education: The effects on knowledge of pregnancy related malaria and preventive practices in women of reproductive age in Edo State, Nigeria - Al Atabbi Hind; Scheelbeek Pauline FD; Mens Petra F; Enato Ehijie FO (BMC, 2011)
Abstract Background There is limited uptake of measures to prevent malaria by pregnant women in Nigeria which is often related to the lack of knowledge on Malaria in Pregnancy (MIP) and its effects on mother and foetus. This study, explored peer to peer education as a tool in raising knowledge of MIP among women of child bearing age. Methods 1105 women of child bearing age were interviewed in their households using a structured questionnaire about their knowledge of malaria in general, MIP and use of preventive measures. Thereafter, a peer education campaign was launched to raise the level of knowledge in the community. The interviews were repeated after the campaign and the responses between the pre- and post-intervention were compared. Results In the pre-assessment women on average answered 64.8% of the question on malaria and its possibility to prevent malaria correctly. The peer education campaign had a significant impact in raising the level of knowledge among the women; after the campaign the respondents answered on average 73.8% of the questions correctly. Stratified analysis on pre and post assessment scores for malaria in general (68.8 & 72.9%) and MIP (61.7 & 76.3%) showed also significant increase. Uptake of bed nets was reported to be low: 11.6% Conclusion Peer education led to a significant increase in knowledge of malaria and its prevention but we could not asses its influence on the use of preventive measures.